School-university-community collaboration for civic education and engagement in the democratic project - Reardon, R. Martin; Leonard, Jack, 1948- (Current perspectives on school/university/community research, 2022)
"The Campaign for the Civic Mission of Schools (2011) lamented the "lack of high-quality civic education in America's schools [that] leaves millions of citizens without the wherewithal to make sense of our system of government" (p. 4). Preus et al. (2016) cited literature to support their observation of "a decline in high-quality civic education and a low rate of civic engagement of young people" (p. 67). Shapiro and Brown (2018) asserted that "civic knowledge and public engagement is at an all-time low" (p. 1). Writing as a college senior, Flaherty (2020) urged educators to "bravely interpret . . . national, local, and even school-level incidents as chances for enhanced civic education and to discuss them with students in both formal and casual settings" (p. 6). In this eighth volume in the Current Perspectives on School/University/Community Research series, we feature the work of brave educators who are engaged in school-university-community collaborative educational endeavors. Authors focus on a wide range of projects oriented to civic education writ large-some that have been completed and some that are still in progress-but all authors evince the passion for civic education that underpins engagement in the democratic project"--